Numbers and their Cultural Significance: A General Survey of Some Prime Numbers - Pradhan, Jaya Bishnu (Journal of the Institute of Engineering, 2020)
Number is very fundamental entities in mathematics. It is considered that the number is one of the first matheamtical knowledge known to primitive mankind. It is developed with the advancement of human culture and different societies. Different human civilizations developed their own number system in order to solve their everyday activities compatible to them. This paper intended to explore some prime numbers and its significant in hindu culture. From the discussion from cultural, religious perspective and when examining the phenomenon rooted in specific culture, it lead to conclude that the prime numbers are sacred and holy in Hindu culture.